Theoretical-practical notes for thinking about intercultural proposals with vulnerable groups in Spain - Sofía Saulesleja (International Journal of Social Communication, 2024)
This article aims to provide theoretical and practical notions for working with people in situations of "vulnerability", based in the case of Roma women and Muslim migrants in Spain. Sustaining on anthropology of gender, it presents the state of the situation, the structural conditions on which it is urgent to continue insisting if a real transformation is to be pursued, and some practical proposals for applicability. And it is concluded that people in vulnerable situations are crossed by different inequalities and need to enjoy rights to be "integrated" into a majority society